Silybum marianum (L.) Gaertn. A New Record for Dehra Dun - Naithani, H. B.; Gaur, R. C. (Indian Forester, 1969)
Within the limits of the Flora, Brit. Ind. Silybum marianum (L.) Gaertn. (Compositae) has been recorded from West Punjab, Hazara, Peshawar, Jammu and Kashmir. Afterwards, it has occasionally been collected from Chamba and Kulu. Recently it has been found to be naturalising in the Doon Valley on few localised spots. Its sporadic occurrence abruptly in Dehra Dun has been attributed to the possibility of its seeds having accompanied the immigrants from West Punjab, etc., who have settled around the place where it is now spreading. There is similar instance of Lepidium perfoliatum L. recorded before, where the plant, otherwise native of Afghanistan and Baluchistan has been suddenly found growing in Dehra Dun.